The Influence of Liquidity,Profitability,Intensity Inventory,Related Party Debt,And Company Size To Aggressive Tax Rate - Manurung, Adler Haymans (Archives of Business Research, 2019)
This study aims to determine how much influence liquidity, profitability, inventory intensity, related party debt, and firm size on the level of tax aggressiveness. The sample used in this study were 34 manufacturing companies listed on the Indonesia Stock Exchange in the period 2013-2017. Samples were taken by purposive random sampling using certain criteria. Tax aggressiveness is measured by comparing the tax expense and net profit before tax. Liquidity is measured by comparing current assets with current debt. Profitability is measured by comparing net profit after tax and total assets. Inventory intensity is measured by comparing total inventory and total assets. Debt related parties are measured by comparing the amount of related party debt and total assets. Size Company is measured by doing natural market value logarithms. The results of the regression analysis indicate that liquidity, profitability, and firm size have a negative and significant effect on the level of tax aggressiveness. While inventory intensity has a positive and significant effect, but related party debt has no significant effect on the level of tax aggressiveness. Manufacturing companies that are relatively large, liquid, and have high profits often carry out tax aggressiveness by planning to reduce tax costs that must be paid.